A Deconstructive reading of Franz Kafka’s The Trial - Ghosh, Aditi (International Journal of Psychosocial Rehabilitation, 2024)
Kafka’s The Trial, an invisible and a unique piece of fiction, provides the readers with an ambience of uncertaintyand sense of ambiguous and mysterious environment. Written in 1915 and posthumously published in 1925, Kafka’sThe Trial narrates the story of Josef K, a banker, unexpectedly arrested and prosecuted by a remote, inaccessibleand unspecified court system for a crime he says he was unaware of. Josef finds himself in an impossible,nightmarish and tormenting situation here charge which he is accused of and the justice is unknown anduncertain.The Trial it can be interpreted on many levels such as; as a brutal satire of the absurdity of unfair judicialsystems, a frighteningly disturbing examination of the peculiarity of bureaucracy and a vivid demonstration ofhuman weaknesses in face of authority such as the corporate control of the human lives exploiting people’s fear oflosing jobs, the subjection of authority at the hands of accused being, thus destabilizing the hierarchies, decentering between the conscious and subconscious existence of K because the world revolving around himself isunpredictable and unclear. And this deconstructive reading has attempted to limit and differentiate what is “inside”or “outside” the work